Respuesta :
The y intercept would be when x=0,
so, y=0^2+0-6
this will make y= -6
y intercept is at (0,-6)
As for x intercept, this is quadratic so it will have two intercept where y=0
y=x^2+x-6
You'll have to break up the equation to find the answer
0=(x+3)(x-2)
x+3=0 leads to x= -3
x-2=0 leads to x= 2
so the x intercepts are at (2,0) and (-3,0)
so, y=0^2+0-6
this will make y= -6
y intercept is at (0,-6)
As for x intercept, this is quadratic so it will have two intercept where y=0
y=x^2+x-6
You'll have to break up the equation to find the answer
0=(x+3)(x-2)
x+3=0 leads to x= -3
x-2=0 leads to x= 2
so the x intercepts are at (2,0) and (-3,0)
Answer:
C.
x-intercepts: (−3, 0) and (2, 0)
y-intercept: (0, −6)
Step-by-step explanation:
Took the exam